Pengaruh Pemberian Subtitusi Tepung Bulu Ayam Dengan Dedak Halus Terhadap Pertambahan Berat Badan, Konsumsi dan Efisiensi Pakan Domba Lokal Jantan - Mahyuddin Mahyuddin (Jurnal Agripet, 2001)
ABSTRACT. Effect of feeding subtitution of feather meal by rice bran on the body weight gains, feed consumtion, and feed efficiency of the lokal lambs. The experiment was conducted at Experimental Farm, Agriculture Faculty, Syiah Kuala University. Faour lokal male sheep 9-11 months old, with 8,5-11.5 kg weight used as experiment materials. Experimental design of Latin Square (4x4) with the treatments of 0,7 14 and 21 gram of feather powder was applied. The result show that the feed consumption, body weight gains, and feed efficiency has highly significant different (P0.01). The up talking of 21 gram feather powder in ration has increased feed consumption, body, weight gains, and feed efficiency more than of other treatments.